Capital budgeting as a management tool for local authorities and an analysis of Turkish experience - Ünal, Cem Bülent (My University, 1998)
unknown
Keywords: Bütçe; Bütçeleme_İşletmeler; Muhasebe; Yönetim ve yardımcı hizmetler